University Planning Forums Summary Record of Meetings April 1956 — September 1957 - Planning Commission (Planning Commission, 1958)
The session was attended by 132 delegates representing 25 Universities and 70 Planning Forums. Shri Jawaharlal Nehru, Prime Minister, and Chairman of the Planning Commission, inaugurated the Conference. Those present included Shri V. T. Krishnamachari, Deputy Chairman of the Planning Commission, Shri G. L. Nanda, Minister for Planning, Shri C. D. Deshmukh, Finance Minister, Shri K. C. Neogy, Member (Industry), Dr. J. C. Ghosh, Member (Education), Shri S. N. Mishra, Deputy Minister for Planning, Shrimati Durgabai Deshmukh, Chairman of the Central Social Welfare Board, Dr. G. S. Mahajani, Vice-Chancellor of Delhi University, Shri Y. N. Sukthankar, Secretary, Planning Commission, and senior officers of the Planning Commission. Shri S. N. Mishra, in his address of welcome, said: It is a privilege and a pleasure for me to say a few words of welcome to you.
Government of India Planning Commission